PENGARUH EMOTIONAL INTELLIGENCE DAN COWORKER SUPPORT TERHADAP KEPUASAN KERJA MELALUI WORK ENGAGEMENT - Mohammad Tio Pangku Sadewo; Ryan Basith Fasih Khan (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to determine the extent to which work engagement can contribute to the relationship between emotional intelligence and coworker support and job satisfaction. The manufacturing sector in Malang City is developing rapidly and the number of employees is increasing. Every year, companies are increasingly responsible for creating job satisfaction for each of their employees. This research uses quantitative research methods. The study sample in this research was 100 workers in the Malang City manufacturing sector. The data collection technique used a questionnaire distributed to employees in the manufacturing sector in Malang City. The data is processed or processed using smartPLS software 4. From the results of this research it can be concluded that (1) Emotional Intelligence has a significant influence on job satisfaction (2) Coworker Support has a significant influence on job satisfaction (3) Work Engagement can mediate the influence of Emotional Intelligence on job satisfaction (4) Work Engagement cannot mediate the effect of coworker support on job satisfaction.